Building capacity to use and undertake applied health research: establishing a training programme for the health workforce in the West of England. (February 2019) - Sabey, Abigail; Bray, Isabelle; Gray, Selena
Abstract: Objectives: Increasing research capacity is important for health services as part of improving the conduct of high-quality research, which addresses the needs of patients and the public. It is a core function of the 13 Collaborations for Leadership in Applied Health Research and Care (CLAHRCs) established in England between 2008 and 2013. This article reports on the development of an innovative capacity building programme in CLAHRC West over an 18-month period (May 2015 to December 2016). It aims to disseminate the learning from the initiative and share our experience with other CLAHRCs. Study design: The study design was an evaluation of a training programme to build research capacity. Methods: We carried out a training needs assessment among local stakeholders and scoped existing provision of research-related training. This informed the development of a programme of free short courses, which were targeted at health and social care professionals including those working in local authorities and the voluntary sector. We aimed to engage professionals working at all levels in these organisations and to promote interprofessional education, to build a research culture. We engaged a variety of educators to provide a range of 1-day courses at an introductory level, which were accessible to practitioners. Results: During the first 18 months of the training programme, we delivered 31 courses and trained 350 participants. Attendees came from secondary care (20%), voluntary sector (18%) and local authorities (18%). Professionals working in the mental health sector comprised 11% and commissioning 6%. Less well represented were primary care (3%) and community care (4%). The largest professional group was public health, followed by medical, nursing and allied health professionals in approximately equal proportions. Courses were evaluated on a scale of 1 (poor) to 4 (excellent) with the mean being 3.6 (range 3.3–4.0). Conclusions: The training programme has been highly successful with many courses oversubscribed, and all courses being well evaluated by participants. It has met the needs of local professionals for brief, applied training in research, as well as attracting those from other parts of the United Kingdom, suggesting the courses are both appropriate and helping to fill a gap in provision. We are building on this work to further engage audiences working in areas such as the wider determinants of health and commissioning, as well as primary and community sectors. CLAHRCs are uniquely placed to drive a culture change in the use, understanding and application of research across the healthcare community. Highlights: Brief, applied training in research skills engages new audiences from the health workforce. An interprofessional approach to training is valued by participants. CLAHRCs can help meet health professionals' need for research-related CPD.